Replacement of conventional HIV testing with rapid testing: mathematical modelling to predict the impact on further HIV transmission between men. Issue 7 (20th September 2011) - Wilson, David P; Fairley, Christopher K; Sankar, Daniel; Williams, Henrietta; Keen, Phillip; Read, Tim R H; Chen, Marcus Y
Abstract : Background: Rapid HIV testing is not permitted in Australia at the point of care. The authors evaluate the expected net effect of rapid HIV testing compared with standard serology diagnostic tests in terms of onward HIV transmission. Methods: The authors used data for 174 men who had sex with men testing HIV-positive at the Melbourne Sexual Health Centre, Australia, in an agent-based mathematical model. Time of diagnosis is simulated according to conventional enzyme immunoassays or rapid HIV tests, with different window periods. The authors calculated the expected number of additional/averted transmissions due to missed or earlier diagnoses. Results: Fourth generation rapid tests were simulated to miss ∼2–3% of diagnoses compared with conventional fourth generation enzyme immunoassay tests. However, in the remaining 97–98% of cases the rapid test would result in earlier detection of HIV. Overall, the rapid test would reduce time to patients receiving results by a median of ∼12 days. Assuming no changes in testing rates, the introduction of rapid testing diagnostic technologies would prevent one in every 2000–5000 HIV transmissions compared with the conventional diagnostic test. Conclusions: Rapid tests would have a marginal benefit in reducing HIV transmission between men compared with conventional tests under assumptions of no changes in testing frequencies.